Fault Tolerant Air Bubble Sensor using Triple Modular Redundancy Method - Noor Cholis Basjaruddin; Yoga Priyana; Kuspriyanto Kuspriyanto (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2013)
Detection of air bubbles in the blood is important for various medical treatments that use Extracorporeal Blood Circuits (ECBC), such as hemodialysis, hemofiltration and cardio-pulmonary bypass. Therefore a reliable air bubble detector is needed. This study presents the design of a new fault tolerant air bubble detector. Triple Modular Redundancy (TMR) method is used on the sensor section. A voter circuit of the Triple Modular Redundancy will choose one of three sensor outputs to be processed further. Application of Triple Modular Redundancy will prevent errors in the detection of air bubbles, especially if the sensor fails to work.